An investigation of thermal characteristics of a liquid-cooled magnetorheological fluid-based clutch. (May 2015) - Wang, Daoming; Zi, Bin; Zeng, Yishan; Xie, Fangwei; Hou, Youfu
Abstract Thermal characteristics have a critical influence on the working stability, control accuracy, and even service life of a magnetorheological (MR) fluid-based clutch. The present study aims to reveal the thermal characteristics of a proposed liquid-cooled MR clutch under various operating conditions. In this paper, theoretical analyses of heating and heat dissipation of the MR clutch was performed firstly. Then a steady temperature simulation was carried out on the MR clutch, followed by a detailed illustration of the experiments, including MR fluid selection, experimental content and procedure. Thereafter, several heating tests were conducted on the MR clutch, and experimental results concerning the slip power loss of the clutch, temperature variation of the MR fluid, temperature effect on the torque output, and maximum allowable slip power of the clutch were presented and discussed. Experimental results indicate that the proposed liquid cooling method can effectively assist in the heat dissipation of the clutch. Moreover, the temperature increase can lead to a reduction of both the viscous torque and total output torque, especially after long-term service. Furthermore, the allowable steady slip power of the clutch is 35 kW and the allowable transient slip power reaches up to 53.2 kW for a slip time of 120 s under the present experimental conditions.